Loyalty, conscience and tense communion : Jonathan Edwards meets Martha Nussbaum - Hordern, J (2014)
This article responds to Jeffrey Stout’s argument in favour of immanent criticism of religious convictions in public reasoning by examining the affective dimension of religious loyalty and conscience. To this end, a conversation between Jonathan Edwards and Martha Nussbaum is undertaken to explore the basis on which the shared evaluations of religious citizens, especially Christians, should inform public discourse. Whereas the affections of Edwards’s sense of the heart are shown to be epistemologically over-realised and in unsustainable tension with the political implications of his contested social ontology, Nussbaum’s cognitivist theory of emotions improves on Edwards’s by providing a basis for social criticism of religious convictions, but is then found incompatible with her own commitment to a Rawlsian overlapping consensus. Moreover, the political appeal of the Protestant-Stoic conscience she advocates is cast into doubt by considering how Protestant and perhaps Islamic concepts of conscience structure eschatological loyalties that foster not Rawls’s overlapping consensus or even Nigel Biggar’s ‘tense consensus’ but rather the ‘tense communion’ appropriate to twenty-first-century democracies.